Diverse and healthy cropping systems trial protocol - Singh, Love Kumar; Jat, Hanuman Sahay; Bijarniya, Deepak; Mukhopadhyay, Raj; Choudhary, Madhu; Kumar, Manish; Cheesman, Stephanie; Gathala, Mahesh Kumar; Jat, Mangi Lal; Sharma, Parbodh Chander; Krupnik, Timothy J. (International Maize and Wheat Improvement Center, 2022)
On-Farm Research Trials are part of TAFSSA’s Work Package 2 (WP2) activities. WP2 emphasizes farm-and landscape-level interdisciplinary research to identify strategies to increase farmers’ profits and nutritional yields, conserve resources, and maintain or enhance ecological services, while also mitigating greenhouse gas (GHG) emissions from farms and agricultural landscapes. Going beyond typical agriculture-nutrition programs in South Asia, we explore field-and landscape-scale crop and animal farm diversification options supporting multiple benefits, including potential nutritional yield, across environmental and socioeconomic gradients of rice and maize-based farming systems. ICAR-CSSRI (Central Soil Salinity Research Institute) Karnal of Haryana in the northwest Indo-Gangetic Plains of India has been selected as basic research and learning site based on key information on food and nutrition security gaps, environmental stresses, air pollution due to residue burning, groundwater exploitation and climate challenges as well as the prevalence of commodities and farming systems that offer the greatest potential to achieve TAFSSA’s outcomes.